MMP13 Expression Is Increased Following Mutant α-Synuclein Exposure and Promotes Inflammatory Responses in Microglia - Sánchez, Kathryn; Maguire-Zeiss, Kathleen (Frontiers in Neuroscience, 2020)
α-Synuclein is a 140-amino acid protein that readily misfolds and is associated with the Lewy body pathology found in sporadic and genetic forms of Parkinson’s disease. We and others have shown that wild-type α-synuclein is a damage-associated molecular pattern that directly elicits a proinflammatory response in microglia through toll-like receptor activation. Here we investigated the direct effect of oligomeric mutant α-synuclein (A53T) on microglia morphology and activation. We found that misfolded A53T increased quantitative measures of amoeboid cell morphology, NFκB nuclear translocation and the expression of prototypical proinflammatory molecules. We also demonstrated that A53T increased expression of MMP13, a matrix metalloproteinase that remodels the extracellular matrix. To better understand the role of MMP13 in synucleinopathies, we further characterized the role of MMP13 in microglial signaling. We showed exposure of microglia to MMP13 induced a change in morphology and promoted the release of TNFα and MMP9. Notably, IL1β was not released indicating that the pathway involved in MMP13 activation of microglia may be different than the A53T pathway. Lastly, MMP13 increased the expression of CD68 suggesting that the lysosomal pathway might be altered by this MMP. Taken together this study shows that mutant α-synuclein directly induces a proinflammatory phenotype in microglia, which includes the expression of MMP13. In turn, MMP13 directly alters microglia supporting the need for multi-target therapies to treat Parkinson’s disease patients.